Development of Interactive Learning Media with A Malay Culture Nuances and Characteristics of RME on Cube and Cuboid Materials for Junior High School - Tommy Yudha Pratama; Nur Izzati; Okta Alpindo (Universitas Maritim Raja Ali Haji, 2022)
This study aimed to produce interactive learning media with Malay culture nuances and characteristics of RME on Cube and cuboid Materials for Junior High School, valid and practical categories. This research is a solution to the problems arising from the Covid-19 pandemic that applies distance learning so that the learning provided is less appropriate and less effective through the developed learning media; it is expected to help and improve students' understanding. This research starts from the define stage, the design stage, to the development stage by conducting a validity and practicality test. The instruments used are peer assessment questionnaires, expert validation sheets, and practicality questionnaires for educators and students. Data were analyzed by descriptive analysis and quantitative analysis. The data obtained is qualitative, and then the data is converted into quantitative data using MSR. From the Validation of material experts, they obtained an assessment of 80.50% with valid criteria, media expert Validation obtained an assessment of 87.73% with valid criteria, and linguistics expert validation obtained an assessment of 93.01% with valid criteria. For the practicality questionnaire, the teacher's response received an assessment of 92.79 % with practical criteria, and the student response practicality questionnaire received an assessment of 78.27% with practical criteria. The developed product has reached valid and practical criteria. Therefore, this research implies that interactive learning media with Malay culture and RME characteristics is feasible to test for effectiveness.